Analysis of the features, difficulties and advantages of transportation of less-than-truck loads - Savchenko, Lidiia; Lysenko, Mariia; Ihnatova, Anastasiia; Semeriahina, Myroslava (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to analyze the features, difficulties and advantages of transporting groupage cargo. Design/methodology/approach. Basic research methods are the methods of of economic analysis, systematization, synthesis and comparison. Findings. The article gives a clear understanding of the combined, consolidated (less-than-truck loads) cargo and the peculiarities of the carriage of this type of cargo. The advantages of transportation of less-than-truck loads, requirements to them are given. The emphasis has been placed on the economic benefits of consolidated cargo transportation, and conditions are put in place to achieve a reduction in the cost of combined transport. The stages of transportation of less-than-truck loads, participants of the process of the corresponding transportations are considered. The possibilities of consolidation are analyzed – the use of multilevel consolidation and re-consolidation. The emphasis is placed on the need for clear information provision for transportation of combined goods, examples of technical means that can be used in this case are given. Research limitations/implications. The limiting factor in the development of transportation of less-than-truck loads is the complexity of their organization and control, as well as the need for a clear transfer of control over the cargo of each shipper during transportation. It is a well-known fact that the more participants in the transportation process, the more difficult is the transfer of responsibility for the cargo, which complicates the proceedings in disputes for its damage. Originality/value. The significance of the work consists in focusing on the efficiency of transportation of less-than-truck loads and the complexity of its organization and control. Clear understanding of the stages of the process of consolidated goods transportation allows you to see possible bottlenecks of the transportation process.